1989
DOI: 10.1139/x89-068
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of change of saturated sapwood permeability and sapwood conductance with stand development

Abstract: The saturated sapwood permeability (k) of jack pine (Pinusbanksiana Lamb.) from stands of different ages and site qualities was measured using a constant water flow apparatus. Saturated sapwood permeability at the base of the live crown (BLC) increased with age and reached a plateau just beyond 4 × 10−12 m2. The rate at which this plateau was reached, however, was dependent on site quality. Such age-related increases in k can partially explain how trees can maintain similar daytime leaf water potentials at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 0 publications
2
54
1
Order By: Relevance
“…In middle-aged Pinus banksiana trees the trunk resistance was found to increase with decreasing site index. The xylem resistances on the best and poorest sites differed by 2 orders of magnitude (Pothier et al 1989b), a difference similar to that between open-and shade-grown Norway spruce trees in this study. Sapwood resistance of the trunk in spruce from ground level to the upper third of the crown coincides with the values reported for P. banksiana trees of corresponding age and vigour (Pothier et al 1989 b).…”
Section: Discussionsupporting
confidence: 77%
“…In middle-aged Pinus banksiana trees the trunk resistance was found to increase with decreasing site index. The xylem resistances on the best and poorest sites differed by 2 orders of magnitude (Pothier et al 1989b), a difference similar to that between open-and shade-grown Norway spruce trees in this study. Sapwood resistance of the trunk in spruce from ground level to the upper third of the crown coincides with the values reported for P. banksiana trees of corresponding age and vigour (Pothier et al 1989 b).…”
Section: Discussionsupporting
confidence: 77%
“…The k Shoot will also be inversely proportional to the length (or height, h) of the shoot for the same length-and area-specific sapwood conductivity (defined as flow rate per pressure gradient per sapwood area). Limited information available from a study on pine shows that variations in sapwood conductivity are weakly related to age between 40 and 140 years, the range of ages for the beech in this study (Pothier, Margolis & Waring 1989b;Pothier et al 1989a), and direct measurements of hydraulic conductance are consistent with an inverse relationship to height (Mencuccini & Grace 1996). Combining these proportionalities gives:…”
Section: Responses Of G Si To Environmental Variablesmentioning
confidence: 55%
“…Pothier et al [52] found that sapwood permeability increases with increasing age, which is partly due to an increase in tracheid length. Pothier et al [53] [38] and tree age [75], due to differing nutrition, or due to acclimation along light gradients within the canopy [48,49] and if the distribution of tree structures within stands are considered.…”
Section: Discussionmentioning
confidence: 99%